Strategic Financial Analysis of Company in the Sphere of International Medical Tourism - S. A. Boronenkova; S. A. Tanaeva (Учёт. Анализ. Аудит)
Nowadays international medical tourism is getting increasingly popular in Russia. The number of companies specializing in outbound tourism is growing every year despite the tightening of the Government requirements to them. The paper focuses on the comparative analysis of the main costs in the formation of a medical tourist product, as well as the current financial situation of the company on the example of a travel agency LLC “Medical Treatment Abroad — LEZARD”. The methodological basis of the study is the matrix of financial strategies of Franchon and Romanet. There are three main indicators of the matrix being used as the calculation parameters: the calculation of financial activity, economic activity, financial and economic activity of the company. The authors tried to give a conclusion about the prospects for the development of the subject according to the analysis results of the company as well as nationwide. The paper formulated some guidances how to expand the range of the company’s products in order to maximize profits and possible bankruptcy of the company. The theoretical and practical significance of the study lies in the fact from the analysis results make it possible to forecast concerning the future stability and financial sustainability of LLC “UCIC Treatment Abroad”.